Photonic Jet Writing of Quantum Dots Self‐Aligned to Dielectric Microspheres. Issue 9 (16th July 2021) - Ristori, Andrea; Hamilton, Travis; Toliopoulos, Dimosthenis; Felici, Marco; Pettinari, Giorgio; Sanguinetti, Stefano; Gurioli, Massimo; Mohseni, Hooman; Biccari, Francesco
Abstract: Owing to their ability to generate non‐classical light states, quantum dots (QDs) are very promising candidates for the large‐scale implementation of quantum information technologies. However, the high photon collection efficiency demanded by these technologies may be impossible to reach for "standalone" semiconductor QDs, embedded in a high‐refractive index medium. In this work a novel laser writing technique is presented, enabling the direct fabrication of a QD self‐aligned—with a precision of ±30 nm—to a dielectric microsphere. The presence of the microsphere leads to an enhancement of the QD luminescence collection by a factor 7.3 ± 0.7 when an objective with 0.7 numerical aperture is employed. This technique exploits the possibility of breaking the N−H bonds in GaAs 1 − x N x :H by a laser light, obtaining a lower‐bandgap material, GaAs 1 − x N x . The microsphere, deposited on top of a GaAs 1 − x N x :H/GaAs quantum well, is used to generate a photonic nanojet, which removes hydrogen exactly below the microsphere, creating a GaAs 1 − x N x QD at a predefined distance from the sample surface. Second‐order autocorrelation measurements confirm the ability of the QDs obtained with this technique to emit single photons. Abstract : Quantum dots (QDs) are very promising candidates for the large‐scale implementation of quantum information technologies. A novel laser writing technique, harnessing the properties of dielectric microspheres and the effects of hydrogen in dilute nitrides, enables the fabrication of GaAs1‐ x Nx QDs. These QDs are self‐aligned to the microspheres, leading to a 7‐fold (with a NA = 0.7 objective) enhancement of their luminescence collection.